2019
DOI: 10.1172/jci.insight.127527
|View full text |Cite
|
Sign up to set email alerts
|

Hematopoietic stem cell transplant effectively rescues lymphocyte differentiation and function in DOCK8-deficient patients

Abstract: Biallelic inactivating mutations in DOCK8 cause a combined immunodeficiency characterized by severe pathogen infections, eczema, allergies, malignancy, and impaired humoral responses. These clinical features result from functional defects in most lymphocyte lineages. Thus, DOCK8 plays a key role in immune cell function. Hematopoietic stem cell transplant (HSCT) is curative for DOCK8 deficiency. While previous reports have described clinical outcomes for DOCK8 deficiency following HSCT, the effect on lymphocyte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
39
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(40 citation statements)
references
References 79 publications
1
39
0
Order By: Relevance
“…Therefore, among all the treatments options currently available for PID patients, hematopoietic stem cell transplantation (HSCT) is the most curative and reliable one. Multiple studies have reported significant efficacy of HSCT in different PID associated with synaptic defects (92, 201,[298][299][300][301][302][303][304][305]. However, HSCT is a heavy surgical procedure that requires prior immunosuppressive conditioning.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, among all the treatments options currently available for PID patients, hematopoietic stem cell transplantation (HSCT) is the most curative and reliable one. Multiple studies have reported significant efficacy of HSCT in different PID associated with synaptic defects (92, 201,[298][299][300][301][302][303][304][305]. However, HSCT is a heavy surgical procedure that requires prior immunosuppressive conditioning.…”
Section: Discussionmentioning
confidence: 99%
“…The age range of the healthy donors is from birth (cord blood) to ~65 years old. These data are compiled from findings previously reported in the following publications: (2937, 3944).…”
Section: Introductionmentioning
confidence: 99%
“…Assessing respiratory burst in phagocytes using oxidation of fluorescent probes such as dihydrorhodamine 123 (DHR) following leukocyte activation in vitro is the gold standard for diagnosing individuals with either X-linked or AR forms of chronic granulomatous disease (70), as well as females carriers of the X-linked form of this condition (59). Lastly, the use of cell permeable fluorescent dyes such as carboxyfluorescein succinimidyl ester (CFSE), Cell trace violet and Cell trace yellow, to label intracellular molecules and then track the dilution and concomitant reduction in fluorescence intensity of these dyes with each cell division (71, 72) has enabled detailed analysis of the role of cell division in lymphocyte differentiation and how these events can be uncoupled or compromised in various PIDs (2931, 33, 3537, 40, 58, 60, 7376).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations